Treatment and outcomes of unresectable and metastatic pancreatic cancer treated in public and private Australian hospitals. Issue 4 (23rd November 2021) - To, Yat Hang; Shapiro, Julia; Wong, Rachel; Thomson, Benjamin; Nagrial, Adnan; Mendis, Shehara; Gibbs, Peter; Shapiro, Jeremy; Lee, Belinda
Abstract: Background: Prior studies have reported for several cancer types that treatment in the private sector is associated with improved survival outcomes. Data for patients with locally advanced unresectable and metastatic pancreatic ductal adenocarcinoma (PDAC) have not previously been reported. Methods: Analysis of patients from January 2016 to June 2020 registered to a multicentre prospective cancer database. Baseline demographic and clinicopathologic characteristics were compared. The Kaplan–Meier method was used to compare overall survival (OS). Multivariate Cox and logistic regression analyses were used to determine predictors of mortality and first‐line chemotherapy treatment, respectively. Results: Of 822 patients, 22.5% received private care. Private patients were older (median 71.5 vs. 68.9 years, p  ≤ .05), had better performance status (ECOG 0 to 1: 82.2 vs. 73.5%, p  = .05) and more likely to reside in an area with high socioeconomic advantage (67.0 vs. 19.6%, p  ≤ .01). Private patients were more likely to receive first‐line chemotherapy (69.7 vs. 54.2%, p  ≤ .01) with logistic regression demonstrating private care (OR: 1.87, 95% CI: 1.20 to 2.97) as an independent predictor of receiving chemotherapy. Private patients had prolonged survival (median OS: 9.2 vs. 6.9 months, HR 1.2, p  = .05). Receiving first‐line chemotherapy was an independent predictor of mortality, but private care was not. Conclusions: Care in the private system is associated with improved OS, with higher uptake of first‐line chemotherapy appearing to be the main contributor. Given the discrepancy, further studies are needed to determine what factors are driving this difference. Abstract : Graphical abstract: Treatment of metastatic and locally unresectable pancreatic cancer in the private health sector is associated with improved median overall survival compared to the public sector.